Immunity Rights of Experts Who Provide Statements in Trials (Study Decision No: 47/Pdt.G/LH/2018/PN Cbi) - Mansyah, Muh Sutri; Suhartono, Rizki Mustika; Salad, Hariasi; Dewi, Rasmala; Bimasakti, David Haryo (Universitas Negeri Semarang, 2023)
This paper investigates the critical issue of immunity rights for experts who provide statements in trials, with a specific focus on the analysis of Decision No: 47/Pdt.G/LH/2018/PN Cbi. Employing a normative research approach, the study adopts a comprehensive methodology, encompassing a case and statutory perspective alongside grammatical and systematic interpretation. The pivotal finding of the research centers on the rejection of a lawsuit by the Panel of Judges, attributing it to the absence of relative competence in the presented case. Notably, the decision contains a notable directive, proposing that